Global distributions and strain diversity of avian infectious bronchitis virus: a review - Bande, Faruku; Arshad, Siti Suri; Omar, Abdul Rahman; Bejo, Mohd Hair; Mahmuda, Aliyu; Nair, Venugopal (Cambridge University Press, 2017)
The poultry industry faces challenge amidst global food security crisis. Infectious bronchitis is one of the most important viral infections that cause huge economic loss to the poultry industry worldwide. The causative agent, infectious bronchitis virus (IBV) is an RNA virus with great ability for mutation and recombination; thus, capable of generating new virus strains that are difficult to control. There are many IBV strains found worldwide, including the Massachusetts, 4/91, D274, and QX-like strains that can be grouped under the classic or variant serotypes. Currently, information on the epidemiology, strain diversity, and global distribution of IBV has not been comprehensively reported. This review is an update of current knowledge on the distribution, genetic relationship, and diversity of the IBV strains found worldwide.